(untitled) (Journal of International Studies, 2015)
The 9/11 attacks perpetrated against the United States has impacted Malaysia-US relations in a signifi cant way. Despite the murmurs of disapproval and condemnation from the international community that characterised the controversial US invasion of Iraq in 2003, Malaysia-US relations have grown from strength to strength. It is suggested that Malaysia’s political leadership is one of the contributing factors that has shaped the growing bilateral relationship. Hence, the purpose of this paper is to examine the role played by Malaysia’s political establishment in nurturing the progressive relations between the two countries. Certainly, both Malaysia and the US exist in a dynamic global world that is constantly shaped by events that take place within their surrounding environment.